2014
DOI: 10.1111/nmo.12415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of esophagogastric junction relaxation by 4‐second Integrated Relaxation Pressure in achalasia using High Resolution Manometry with water‐perfused catheters

Abstract: Cut-off values for 4-s IRP defined using HREPT with solid-state catheters are not adequate for diagnosing esophageal achalasia with water-perfused systems. A lower value, i.e., 6.5 mmHg, is suggested for this equipment. The diagnostic criteria of esophageal achalasia should be modified for HREPT performed with water-perfused systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…Other studies using 22‐channel water‐perfused catheters have shown a larger difference in normative thresholds . In the study by Ortiz et al . 695 controls without achalasia and 47 patients with untreated achalasia were evaluated.…”
Section: Differences Between Hrm Systems Affect Normal Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using 22‐channel water‐perfused catheters have shown a larger difference in normative thresholds . In the study by Ortiz et al . 695 controls without achalasia and 47 patients with untreated achalasia were evaluated.…”
Section: Differences Between Hrm Systems Affect Normal Valuesmentioning
confidence: 99%
“…Other studies using 22-channel water-perfused catheters have shown a larger difference in normative thresholds. 32,34 In the study by Ortiz et al 34 695 controls without achalasia and 47 patients with untreated achalasia were evaluated. They concluded that for their system the cutoff value of 15 mmHg for IRP4 was not adequate for diagnosing esophageal achalasia as 23 of the 47 achalasia patients had an IRP4 less than 15 mmHg.…”
Section: Differences Between Hrm Systems Affect Normal Valuesmentioning
confidence: 99%
“…The HRM studies were performed with the patient supine after an 8-hour fast, using equipment with perfused catheters, based on our unit's protocol. 4 Manometric diagnosis was based on the international Chicago classification criteria. 5 The HRM showed lower esophageal sphincter (LES) hypertonia with pathological relaxation in all cases.…”
mentioning
confidence: 99%
“…Кроме того, в исследованиях по сравнению манометрических показателей, полученных при исследовании твердотельным и водно-перфузионным катетером, было показано, что если значения DL, DCI практически не зависят от типа катетера, то результаты давления покоя НПС и ВПС значительно разнятся при использовании водно-перфузионного и твердотельного катетеров [26][27][28][29]. Это связано с разным диаметром катетеров, более высокой скоро-…”
Section: интерпретация результатов в зависимости от типа аппаратуры unclassified